2008
DOI: 10.1111/j.1600-0706.2008.16540.x
|View full text |Cite
|
Sign up to set email alerts
|

A neutral‐niche theory of nestedness in mutualistic networks

Abstract: Recently, there has been a vigorous interest in community ecology about the structure of mutualistic networks and its importance for species persistence and coevolution. However, the mechanisms shaping mutualistic networks have been rarely explored. Here we extend for the first time the neutral theory of biodiversity to a multi trophic system. We focus on nestedness, a distinctive pattern of mutualistic community assembly showing two characteristics, namely, asymmetrical specialization (specialists interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
139
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(156 citation statements)
references
References 42 publications
10
139
4
3
Order By: Relevance
“…These studies also showed that the observed interactions are better predicted by simulations when other factors are included together with the abundance, such as phenological overlap [9,11,12], morphological matches among species [14] or the phylogenetic relationship, which ultimately influences the traits of the species [15]. In this sense, species traits affect the possibility of interactions by creating forbidden links in the community, although their importance seems to be secondary in comparison with species abundance.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These studies also showed that the observed interactions are better predicted by simulations when other factors are included together with the abundance, such as phenological overlap [9,11,12], morphological matches among species [14] or the phylogenetic relationship, which ultimately influences the traits of the species [15]. In this sense, species traits affect the possibility of interactions by creating forbidden links in the community, although their importance seems to be secondary in comparison with species abundance.…”
Section: Introductionmentioning
confidence: 84%
“…In the context of ecological networks, neutral-based processes (often treated as neutrality, [9]) presume that species are ecologically equivalent. This means that individuals interact randomly in the community independently of their traits (specializations), thus more abundant species interact with more partners and with higher frequency than rarer species [8][9][10][11][12]. On the other hand, the concept of forbidden links assumes that niche-based processes constrain the interactions by means of matches and mismatches on the ecological traits of species [1,[3][4][5][6]9,10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this hypothesis does not fully account for some properties observed in networks, such as, the extent that species with a lower degree have interactions with a subset of the partners of species with a high degree, referred to as nestedness. For example, relative species abundance explains only 60-70% of the nestedness of two networks for plant-frugivore communities in southern Spain, with the 30-40% unexplained nestedness suggesting that the abundance and forbidden links hypotheses (and likely more) are not mutually exclusive and may work in concert to determine network structure and variability (Krishna et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Resource tracking can create scenarios where local abundances of frugivores increase as certain resources increase, which may, in turn, increase the likelihood of interactions with multiple plant species in the area that are fruiting at the same time; a scenario that is predicted by the abundance hypothesis. Multiple studies have suggested that resource tracking may play a role in the temporal dynamics of SD networks (Krishna et al, 2008;Carnicer et al, 2009;Yang et al, 2013). However, the influence resource tracking has on SD networks has not been explicitly explored, and, therefore, theory of how resource tracking may influence networks is still being developed (Figure 1).…”
Section: Introductionmentioning
confidence: 99%